Mixed adhesive composition for shielding electromagnetic waves, preparation method of mixed adhesive for shielding electromagnetic waves, and mixed adhesive film for shielding electromagnetic waves

By using a mixed binder composition of conductive metal particles, chemical modified graphene, bonding resin and curing agent in the bonding membrane, combine the functional groups of chemical modified graphene and bonding resin and add a second graphene It solves the problems of high shielding performance, flexibility, thin layer and high temperature stability in the existing technology, and achieve efficient electromagnetic wave shielding effects.

CN114502681BActive Publication Date: 2025-01-28BESTGRAPHENE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080002491.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-09
Publication Date
2025-01-28
Estimated Expiration
2040-09-09

AI Technical Summary

Technical Problem

The existing bond film used to shield electromagnetic waves is difficult to take into account high shielding performance, flexibility, thin layering and high temperature stability due to the tendency of lightweight and shortening and multifunctionalization in electronic devices.

Method used

A mixed binder composition containing conductive metal particles, chemical modified graphene, bonding resin, and curing agent is combined through the functional unity of chemical modified graphene and bonded resin to improve the conductivity and adhesion of the bonding layer Jacking power, and through the addition of second graphene, further optimize the electromagnetic wave shielding performance and high temperature stability of the bonding layer.

Benefits of technology

The adhesive layer of high adhesion, low -thin layer resistance and high temperature stability, significantly improved electromagnetic wave shielding performance, and is suitable for flexible and thin -layered electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114502681B_ABST
    Figure CN114502681B_ABST
Patent Text Reader

Abstract

The present invention relates to a mixed adhesive composition for shielding electromagnetic waves, characterized in that it comprises conductive metal particles, a first graphene, an adhesive resin and a curing agent, wherein the first graphene is a chemically modified graphene, and the adhesive resin is combined with a functional group of the chemically modified graphene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a mixed adhesive composition for shielding electromagnetic waves, a preparation method of the mixed adhesive for shielding electromagnetic waves and a mixed adhesive film for shielding electromagnetic waves. Background Art

[0002] Recently, as electronic devices are becoming lighter, smaller, and more multifunctional, which is a trend in the development of electronic devices, research on miniaturization and high integration of electronic components provided in electronic devices is being actively conducted.

[0003] As such electronic components become smaller and more highly integrated, not only does more heat get generated in the electronic components, but also as the distances between the electronic components get closer, electromagnetic waves generated in one electronic component can affect another adjacent electronic component, thereby hampering normal operation.

[0004] In order to prevent the influence of electromagnetic waves, shielding members are used to surround electronic components or printed circuit boards to block electromagnetic waves. Electromagnetic wave shielding members include metal films, conductive pastes, conductive films, etc., which have excellent electrical conductivity.

[0005] In particular, in the case of multilayer flexible printed circuit boards (FPCBs) such as rigid-flex boards, there is an increasing demand for shielding component products in the form of adhesive films that have excellent step-filling properties and conductive resistance.

[0006] The adhesive film for shielding electromagnetic waves is composed of an electromagnetic wave shielding layer and an adhesive layer. However, due to the trend of electronic devices becoming thinner, lighter, shorter, and more multifunctional and wearable, the shielding layer is also required to be flexible and thin. As for the flexibility and thinness of the shielding layer, the shielding performance and the flexibility and thinness requirements are in a trade-off relationship. Therefore, in order to supplement the insufficient shielding performance, the adhesive layer also needs to have high shielding performance.

[0007] In order to improve the shielding performance of the adhesive layer, if a high concentration of conductive metal particles such as silver or copper powder is filled, the coating workability is reduced due to the increase in viscosity, or the adhesive layer becomes uneven due to the sedimentation of the conductive metal particles, or the shielding layer becomes thicker. Furthermore, there is a problem of reduced high temperature stability.

[0008] In order to solve the above-mentioned problem, it is necessary to reduce the viscosity of the composition forming the bonding layer, and improve high temperature stability. However, if the amount of the solvent is only increased in order to reduce the viscosity, the solvent added to the bonding layer composition is scattered due to heat, so that there is a problem of generating a void. If a void is generated, not only the electromagnetic wave shielding performance of the bonding film is reduced, but also the problem of reduced shielding performance occurs during use due to reduced heat resistance.

[0009] Therefore, there is a need for a new adhesive composition for use in an adhesive film for shielding electromagnetic waves that can solve such problems. Summary of the invention

[0010] Technical issues

[0011] The present invention relates to a mixed adhesive composition for shielding electromagnetic waves used in the preparation of an adhesive layer as a structure of an adhesive film for shielding electromagnetic waves. Its purpose is to provide a mixed adhesive composition for shielding electromagnetic waves that can be used to prepare an adhesive layer having electromagnetic wave shielding performance and having high bonding strength and high-temperature stability.

[0012] On the other hand, other objects not explicitly stated in the present invention can be further considered within the scope that can be easily inferred from the following detailed description and its effects.

[0013] Solutions to the problem

[0014] In order to achieve the above-mentioned problems, a mixed adhesive composition for shielding electromagnetic waves used in preparing an adhesive layer as one structure of an adhesive film for shielding electromagnetic waves is proposed.

[0015] A mixed adhesive composition for shielding electromagnetic waves according to one embodiment of the present invention is characterized in that it comprises conductive metal particles, a first graphene, an adhesive resin and a curing agent, wherein the first graphene is a chemically modified graphene, and the adhesive resin is combined with a functional group of the chemically modified graphene.

[0016] In one embodiment, the present invention is characterized in that the content of the above-mentioned conductive metal particles is 10-56wt%, the content of the above-mentioned first graphene is 0.005-0.1wt%, the content of the above-mentioned binding resin is 10-45wt%, and the content of the above-mentioned curing agent is 1-10wt%.

[0017] In one embodiment, the present invention is characterized in that it further comprises a second graphene, and the second graphene is non-oxidized graphene.

[0018] In one embodiment, the present invention is characterized in that the content of the second graphene is 0.01-1 wt %.

[0019] In one embodiment, the present invention is characterized in that the conductive metal particles are in a flake shape or a dendrite shape.

[0020] In one embodiment, the present invention is characterized in that the functional group is at least one selected from the group consisting of amine, amide, alcohol, epoxide, azide, thiol, anhydride and carboxyl.

[0021] Another embodiment of the present invention provides a method for preparing a mixed adhesive for shielding electromagnetic waves, which comprises: a step of preparing a first colloid in which a first graphene is dispersed; a step of pre-dispersing the first colloid and an adhesive resin in a solvent; a step of mainly dispersing metal particles in the solvent in which the adhesive resin is pre-dispersed; and a step of adding a curing agent to form an adhesive to obtain the main dispersion of the metal particles, wherein the first graphene is chemically modified graphene, and the adhesive resin is combined with functional groups of the chemically modified graphene.

[0022] In another embodiment, the present invention is characterized in that the step of preparing a first colloid includes: treating a graphite sheet with an oxidant and, after impregnation, irradiating with microwaves to prepare expanded graphite oxide; exfoliating the expanded graphite oxide to prepare graphene oxide; mixing the prepared graphene oxide with deionized water to prepare a graphene oxide suspension; and adding an additive for modifying graphene into the graphene oxide suspension, and after stirring, preparing a first colloid containing chemically modified graphene through a large-capacity circulating ultrasonic dispersion system, wherein the additive is an additive capable of forming a functional group of the chemically modified graphene, and the functional group of the chemically modified graphene can be at least one selected from the group consisting of amine, amide, ethanol and carboxyl.

[0023] In another embodiment, the present invention is characterized in that the step of achieving the main dispersion is performed by mixing the second colloid in which the second graphene is dispersed with the solvent, and the second graphene is non-oxidized graphene. In this case, the present invention is characterized in that the step of preparing the second colloid includes: preparing expanded graphite; preparing graphene flakes by exfoliating the expanded graphite; and preparing the second colloid by dispersing the exfoliated graphene flakes.

[0024] Another embodiment of the present invention is a hybrid adhesive film for shielding electromagnetic waves, which comprises a shielding layer and an adhesive layer, wherein the adhesive layer contains conductive metal particles, a first graphene and an adhesive resin, wherein the first graphene is a chemically modified graphene, and the adhesive resin is combined with functional groups of the chemically modified graphene.

[0025] Effects of the Invention

[0026] The mixed adhesive composition for shielding electromagnetic waves according to one embodiment of the present invention comprises conductive metal particles, chemically modified graphene, an adhesive resin and a curing agent, whereby the prepared adhesive layer maintains high adhesive force and reduces sheet resistance, thereby improving shielding performance. In addition, it also has the advantage of significantly improving high temperature stability.

[0027] On the other hand, it should be noted that even if the effects are not explicitly stated here, the effects described in the following description and their tentative effects expected by the technical features of the present invention will be handled in the same manner as the effects described in the description of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM picture of a plurality of metal particles used in the hybrid adhesive composition for shielding electromagnetic waves of the present invention.

[0029] Figure 2 A reference diagram for briefly illustrating the reaction between chemically modified graphene and resin in the hybrid adhesive film for shielding electromagnetic waves of the present invention.

[0030] Figure 3 The present invention is a simplified flow chart of the method for preparing the mixed adhesive for shielding electromagnetic waves.

[0031] Figure 4 It is a schematic perspective view showing the structure of the hybrid adhesive film for shielding electromagnetic waves according to the present invention.

[0032] Figure 5 It is a simplified schematic diagram showing the structure of the adhesive layer of the hybrid adhesive film for shielding electromagnetic waves of the present invention.

[0033] Figure 6 The optical microscope images (c) show an adhesive (a) prepared using the adhesive composition according to one embodiment of the present invention, a prototype (b), and a surface of the formed adhesive layer.

[0034] It should be noted that the attached drawings are provided as references for understanding the technical concept of the present invention, and the protection scope of the present invention will not be limited thereby. DETAILED DESCRIPTION

[0035] Hereinafter, the structures of the present invention and the effects derived from these structures are observed in accordance with various embodiments of the present invention with reference to the accompanying drawings. In the process of describing the present invention, the relevant well-known functions are matters known to ordinary technicians in the technical field to which the present invention belongs. If it is judged that it is unnecessary to confuse the gist of the present invention, the detailed description of them will be omitted.

[0036] A mixed adhesive composition for shielding electromagnetic waves according to an embodiment of the present invention (hereinafter referred to as “adhesive composition”) includes conductive metal particles, a first graphene, an adhesive resin, and a curing agent.

[0037] The conductive metal particles impart conductivity to the prepared adhesive layer, thereby playing the main role of the adhesive layer in shielding electromagnetic waves. As the conductive metal particles, silver (Ag) or copper (Cu) coated with silver on the surface can be used, but the present invention is not limited thereto, and gold or platinum, nickel, etc. can also be used. In order to improve the connectivity relative to the same weight, the conductive metal particles can use anisotropic conductive metal particles. For example, Figure 1 As shown, the conductive metal particles may be in a flake shape or a dendrite shape. Figure 1 Part (a) is a copper sheet coated with silver. Figure 1 The portion (b) is a copper in the shape of a dendrite coated with silver on the surface. The size of the conductive metal particles can be 3 to 30 um. However, in general, the thickness of the adhesive layer is 5 to 15 um, and more preferably, the conductive metal particles can use conductive metal particles with a center particle size (D50) of 5 to 12 um.

[0038] The content of the conductive metal particles can be 10 to 56 wt % of the entire adhesive composition. When the content of the conductive metal particles is less than 10 wt %, the sheet resistance increases. That is, there is a problem of low shielding performance. In addition, when the content of the conductive metal particles is greater than 56 wt %, not only does the bonding force decrease to less than 1.0 kgf / cm, but also the processability is significantly reduced.

[0039] On the other hand, when the conductive metal particles are copper particles coated with silver, the content of silver in the conductive metal particles is preferably 5 wt % to 30 wt %. When the content of silver is less than 5%, the sheet resistance and high temperature stability of the prepared adhesive layer are too low, and when the content of silver is more than 30%, the effect of reducing the sheet resistance is minimal.

[0040] The bonding resin uses a resin that can impart bonding properties to the bonding layer after curing. Epoxy resin or polyurethane resin can be used as the bonding resin. In addition, a resin that can be used as a bonding agent can also be used. As epoxy resin, there are bisphenols (A type, F type), phenolic varnish (Phenol novolac) class, o-cresol phenolic varnish (Cresol novolac) class, multifunctional epoxy resin, amine epoxy resin, heterocyclic epoxy resin, substituted epoxy resin, naphthol epoxy resin and their derivatives. The bonding resin used by the binder composition of the present invention can be a resin combined with the functional group of the chemically modified graphene used as the first graphene described below. This will be described later.

[0041] The content of the adhesive resin is 10 to 45 wt % of the entire adhesive composition. When the content of the adhesive resin is less than 10 wt %, the adhesive force is reduced to less than 1.0 kgf / cm, and when the content of the adhesive resin is greater than 45 wt %, not only is it impossible to further expect an increase in the adhesive force because sufficient adhesive force has been ensured, but there is also a problem that the proportion of the components that contribute to the shielding performance is relatively reduced.

[0042] The curing agent can be appropriately selected according to the type of the binder resin. ) adhesive, the adhesive composition may contain both a curing agent and a bonding resin. ) binder, the curing agent is formed separately from the binder resin. As the curing agent, dicyandiamide, imidazole, amine, amide, polyphenol, phenolic resin, phenolic ether resin, etc. can be used. The content of the curing agent can be 1 to 10wt% of the entire binder composition. The content of the curing agent can be appropriately adjusted according to the content of the binder resin.

[0043] Furthermore, the adhesive composition of the present invention may further include a catalyst, an additive, and a surfactant, and the additives may include a curing accelerator, an organic / inorganic coupling agent, a toughening agent, a leveling agent, and the like.

[0044] As the catalyst, phosphine or boron curing catalysts and imidazole catalysts can be used. As the phosphine curing catalyst, triphenylphosphine can be used, but the present invention is not limited thereto. The content of the catalyst can be less than 1wt% of the entire binder composition.

[0045] As the dispersant, a phosphoric acid dispersant can be used, for example, RE-610 from Solvay, BYK-103 from BYK, etc. As the organic / inorganic coupling agent, a silane coupling agent (3-glycid-oxypropyl trimethoxy-silane (GPTMS), etc.) can be used.

[0046] In addition, curing accelerators, toughening agents, leveling agents, etc. may be included as additives, and they may be selected from known additives. The content of the additives may be less than 3 wt % of the binder composition. In addition, a surfactant may be included for the purpose of dispersion stability, and the content of the surfactant may be 0.1 to 5 wt % of the binder composition.

[0047] As the solvent, amide solvents such as dimethylacetamide and N-methyl-2-pyrrolidone; ethanol solvents such as methanol, ethanol, isopropanol; aromatic solvents such as toluene and xylene; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone; ester solvents such as ethyl acetate, etc. can be used. The content of the solvent can be 20 to 62wt% of the adhesive composition. When the content of the solvent is less than 20wt%, there is a problem of reduced fluidity and processability. When the content of the solvent is greater than 62wt%, there is a problem of reduced shielding performance and reduced stability caused by the occurrence of voids.

[0048] The additive composition of one embodiment of the present invention is characterized in that it comprises a first graphene. The first graphene is a chemically modified graphene, and in particular, the surface of the chemically modified graphene comprises a functional group that can be combined with a binder resin. Figure 2 As shown, in the first graphene included in the additive composition of one embodiment of the present invention, the binding resin is combined with the functional group. For example, the functional group of the chemically modified graphene can be an amine, a hydroxyl, an amide, an azide, an epoxide, a thiol, an anhydride and a carboxyl group. In the case where the binding resin is bisphenol A diglycidyl ether, the functional group of the chemically modified graphene can be an anhydride, an amine, an amide, a thiol, a carboxyl acid, pyridine, an azide, an acrylate, an epoxide, etc., and the functional group of the chemically modified graphene is combined with bisphenol A diglycidyl ether.

[0049] As shown in the background art, in order to improve the shielding performance of the adhesive layer, a large amount of conductive metal particles need to be included, and if the amount of conductive metal particles increases, there is a problem of reduced operability. In addition, the increase of conductive metal particles occupying the adhesive layer not only reduces the adhesive force of the adhesive layer, but also reduces the physical properties. For example, the increase of conductive metal particles will lead to the problem of reduced stability in high temperature and moisture-resistant environments.

[0050] The additive composition of one embodiment of the present invention uses the first graphene to improve the connectivity between the conductive metal particles contained in the adhesive layer, thereby significantly improving the shielding performance of the adhesive layer. That is, even if the content of the conductive metal particles is not excessively increased, the shielding performance of the adhesive layer is significantly improved, so there is no problem of reducing operability and reducing bonding force due to excessive conductive metal particles. Moreover, as described later, it has the advantages of increasing bonding force due to the participation of the chemical bonding of the first graphene, and improving printing and coating properties by improving mechanical properties and adjusting rheological properties.

[0051] As described above, the first graphene participates in chemical bonding, that is, the functional group of the first graphene is bonded to the bonding resin, thereby having an advantage that the high-temperature stability of the bonding layer is significantly improved.

[0052] The first graphene may use a graphene with a lateral size of 50 nm to 50,000 nm and a thickness of a single layer to multiple layers. At this time, the first graphene may contain 75 to 90 atomic % of carbon (C), 5 to 25 atomic % of oxygen (O), and 2 to 20 atomic % of nitrogen (N). In addition, a graphene charged with a negative charge or a positive charge may be used as the first graphene. The negatively charged first graphene satisfies O / N>1, and the positively charged first graphene satisfies O / N<1.

[0053] The content of the first graphene can be 0.005wt% to 0.1wt% of the binder composition. When the content of the first graphene is less than 0.005wt%, it is almost not helpful to reduce the sheet resistance of the bonding layer. In addition, when the content of the first graphene is greater than 0.1wt%, there is a problem that the bonding force is reduced due to the reaction between the bonding resin and the first graphene, thereby increasing the viscosity and significantly reducing the processability.

[0054] On the other hand, the additive composition of one embodiment of the present invention may further include a second graphene. As the second graphene, a graphene sheet may be used, and preferably, non-oxidized graphene may be used.

[0055] When the first graphene is added in a predetermined amount, the sheet resistance and high temperature stability of the prepared adhesive layer are improved, but if the predetermined amount is exceeded, there is a problem that the adhesive force and processability are significantly reduced. However, when the second graphene is further included, while the adhesive force and processability are maintained, the sheet resistance of the adhesive layer is reduced by the first graphene, and the sheet resistance is further significantly reduced.

[0056] Furthermore, the first graphene, as a modified graphene, has a functional group on its surface, and therefore, the barrier effect of preventing oxidation of conductive metal particles or isolating moisture is insufficient. The additive composition of one embodiment of the present invention uses non-oxidized graphene as the second graphene, thereby preventing oxidation of conductive metal particles and increasing the effect of isolating moisture. Furthermore, the stabilization effect of thermal properties based on the high carbon purity of non-oxidized graphene is excellent. The thickness of the second graphene can be 2 to 10 nm.

[0057] The content of the second graphene can be 0.01 to 1.0 wt % of the binder composition. When the content of the second graphene is less than 0.01 wt %, the shielding performance is slightly improved, and when the content of the second graphene is greater than 1.0 wt %, the bonding force is significantly reduced and the processability is also reduced.

[0058] Figure 3 The present invention is a simplified flow chart of the method for preparing the mixed adhesive for shielding electromagnetic waves.

[0059] Reference Figure 3 The method for preparing a mixed adhesive for shielding electromagnetic waves of the present invention (hereinafter referred to as "the method for preparing the adhesive") includes: a step of preparing a first colloid in which a first graphene is dispersed; a step of preparing a second colloid in which a second graphene is dispersed; a step of pre-dispersing the first colloid and an adhesive resin in a solvent; a step of mainly dispersing metal particles in the pre-dispersed solvent; and a step of adding a curing agent to the mainly dispersed solvent to form an adhesive.

[0060] First, a step of preparing a first colloid in which a first graphene is dispersed is performed.

[0061] Specifically, the steps of preparing the first colloid include: treating a graphite sheet with an oxidant, and after impregnation treatment, irradiating microwaves to prepare expanded graphite oxide; exfoliating the expanded graphite oxide to prepare graphene oxide; mixing the prepared graphene oxide and deionized water to prepare a graphene oxide suspension; and adding an additive for modifying graphene into the graphene oxide suspension, stirring, and preparing a first colloid containing chemically modified graphene through a large-capacity circulating ultrasonic dispersion system.

[0062] The step of preparing expanded graphite oxide can be performed by immersing a graphite sheet in an oxidant for about 30 minutes, and then irradiating the sheet with microwaves at a power of 500 W to 1000 W for 1 minute to 10 minutes. At this time, as the oxidant, a composite oxidant in which two or more of potassium permanganate, sulfuric acid, hydrogen peroxide or phosphoric acid are mixed can be used. As the graphite sheet, a graphite sheet with an average diameter of 100 μm to 500 μm can be used. The graphite oxide obtained by this method is called expanded graphite oxide after microwave treatment (MEGO: Microwaved Expanded Graphite Oxide).

[0063] Then, the step of exfoliating the expanded graphite oxide to prepare graphene oxide is performed. The step of exfoliating the expanded graphite oxide to prepare graphene oxide can be performed by a chemical exfoliation method, for example, an improved method using phosphoric acid, sulfuric acid and potassium permanganate, which is well known in the chemical exfoliation method.

[0064] Then, the step of mixing the prepared graphene oxide and deionized water to prepare a graphene oxide suspension is performed. That is, the exfoliated graphene oxide is dispersed in deionized water (DI water) to prepare a graphene oxide suspension. At this time, the graphene oxide suspension consists of 0.05 wt % to 1 wt % of graphene oxide and the remaining amount of deionized water.

[0065] After preparing the graphene oxide suspension, a step is performed in which an additive for modifying graphene is placed in the graphene oxide suspension, and after stirring (synthesis reaction), a first colloid containing chemically modified graphene is prepared by a large-capacity circulating ultrasonic dispersion system.

[0066] At this time, as additives, substances that can form amino groups, hydroxyl groups, amide groups, azido groups, epoxy groups, mercapto groups, anhydride groups, and carboxyl groups as functional groups of the prepared chemically modified graphene can be used. For example, as additives, organic single molecules or polymers having amino groups, hydroxyl groups, azido groups, anhydride groups, amine groups, mercapto groups, carboxyl acid groups, pyridine groups, azide groups, acrylate groups, and cycloepoxide groups can be used for the modification of graphene. As the organic monomolecule or polymer having an amine group, there can be used an amine selected from ethylenediamine, triethylamine, paraphenylenediamine, 3,3',4,4'-tetraaminobiphenyl, 3,3',4,4'-tetraaminoterphenyl, benzidine, 1 As the organic single molecule or polymer having a hydroxyl group, one selected from the group consisting of polyvinyl alcohol (PVA), hot strong alkaline solutions (KOH, NaOH), hydroxylamine, etc. can be used. As an organic single molecule or polymer having an azide group, one selected from the group consisting of sodium amide, 2-azidoethanol, 3-azidopropyl-1-amine, 4-(2-azidoethoxy)-4-oxobutanoic acid, 2-azidoethyl-2-bromo-2-methylpropanoate, chlorocarbonate, azidocarbonate, dichlorocarbene, carbene, arene and nitrene can be used.When the surface modification reaction is completed, a first colloid containing 1 ton of chemically modified graphene per hour is prepared by a large-capacity circulating ultrasonic dispersion system. At this time, the chemically modified graphene can be dispersed in a solvent.

[0067] Preferably, the solvent used when forming the first colloid may be the same as the solvent of the binder composition.

[0068] For example, the solvent that can be used is water, acetone, methyl ethyl ketone, methanol, ethanol, isopropanol, butanol, ethylene glycol, polyethylene glycol, tetrahydrofuran, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, hexane, cyclohexanone, toluene, chloroform, distilled water, dichlorobenzene, xylene, trimethylbenzene, pyridine, methylnaphthalene, nitromethane, acrylonitrile, octadecylamine, aniline, dimethyl sulfoxide, dichloromethane, diethylene glycol methyl ethyl ether, ethyl acetate, and a mixed solvent thereof.As the auxiliary solvent, amide series N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), aqueous ammonium hydroxide hydrochloric acid solution, α-terpinol, chloroform, methylethyl ketone, formic acid, nitroethane BBB, 2-ethoxy ethanol, 2-methoxy ethanol, 2-butoxyethanol, 2-methoxy propanol, ethylene glycol, acetone, methanol, ethanol, butanol, polyethylene glycol, tetrahydrofuran, hexane, cyclohexanone, toluene, chloroform, distilled water, dichlorobenzene, xylene, trimethylbenzene, pyridine, methylnaphthalene, nitromethane, acrylonitrile, octadecylamine, aniline, dichloromethane, 2-methoxyethanol ethanol), γ-butyrolactone (γGBL), benzyl benzoate, N,N-dimethylacetamide (DMA), 1,3-dimethyl-2-imidazolidinone (DMEU), 1-vinyl-2-pyrrolidone (NVP), 1-dodecyl-2-pyrrolidinone (N12P), dimethyl sulfoxide (DMSO), isopropanol (IPA), 1-octyl-2-pyrrolidone (N8P), diethylene glycol monoethyl ether acetate (DGMEA), propylene glycol monomethyl ether acetate (PGMEA) acetate), propylene glycol monomethyl ether (PGME, propyleneglycol monomethyl ether).

[0069] After preparing the first colloid, a step of pre-dispersing the first colloid and the binding resin in a solvent is performed. The first graphene contained in the first colloid is a chemically modified graphene with a functional group, and the functional group of the chemically modified graphene is combined with the binding resin during the curing process of the binding resin. However, when the conductive metal particles or the second graphene are dispersed together with the first graphene, the dispersibility of the first graphene is reduced, and thus, the effect of improving the connectivity of the conductive metal particles based on the first graphene is significantly reduced. Therefore, in the preparation method of the binder of the present invention, the first graphene is pre-dispersed in a solvent together with the binding resin, so as to increase the interaction between the first graphene and the binding resin, so that the first graphene helps to improve the performance of the bonding layer.

[0070] Then, a step of mainly dispersing the metal particles in the pre-dispersed solvent is performed. At this time, in the main dispersion step, a step of mixing the second colloid dispersed with the second graphene with the above solvent can be performed together. The second graphene can be non-oxidized graphene.

[0071] The step of preparing the second colloid includes: preparing expanded graphite; exfoliating the expanded graphite to prepare graphene flakes; and dispersing the exfoliated graphene flakes to prepare the second colloid.

[0072] The step of preparing expanded graphite oxide can be performed by immersing the graphite sheet in an oxidant for about 30 minutes, and then irradiating it with microwaves at a power of 500W to 1000W for 1 minute to 10 minutes. At this time, as an oxidant, a composite oxidant mixed with two or more of potassium permanganate, sulfuric acid, hydrogen peroxide or phosphoric acid can be used. The average diameter of the expanded graphite sheet prepared in this way is less than 100μm. On the other hand, the step of preparing expanded graphite can also be used by purchasing expanded graphite with an average diameter of less than 100μm. Then, the step of preparing graphene flakes by exfoliating the expanded graphite oxide is performed. The exfoliation of the expanded graphite can be performed in the absence of an oxidant using an intercalator such as a solvent or an ionic base. Then, the step of preparing a second colloid is performed by dispersing the exfoliated graphene flakes.

[0073] Finally, a step of adding a curing agent to the solvent obtained by main dispersion to form a binder is performed. The step of adding a curing agent can be performed during the preparation process or on-site depending on whether it is a one-component or two-component composition.

[0074] Figure 4 A simplified perspective view showing the structure of the hybrid adhesive film for shielding electromagnetic waves of the present invention is shown in FIG. Figure 5It is a simplified schematic diagram showing the structure of the adhesive layer of the hybrid adhesive film for shielding electromagnetic waves of the present invention.

[0075] A hybrid adhesive film for shielding electromagnetic waves (hereinafter referred to as "adhesive film") according to another embodiment of the present invention comprises an adhesive layer 1, a shielding layer 2 (Cu layer, 5 μm), a protective layer 3 and a transparent layer 4. The present invention relates to an adhesive layer 1, such as Figure 5 As shown, the adhesive composition may include a binder resin 10, conductive metal particles 20, and a first graphene 30. Furthermore, the second graphene 40 may be included. The functions of each structure are the same as those described in the adhesive composition.

[0076] Figure 6 The optical microscope images (c) show an adhesive (a) prepared using the adhesive composition according to one embodiment of the present invention, a prototype (b), and a surface of the formed adhesive layer.

[0077] Example 1

[0078] In order to observe the influence of the content of the conductive metal particles, the sheet resistance, adhesive force and process properties were checked while changing the content of the conductive metal particles.

[0079] As the conductive metal particles, 10 wt% of copper coated with silver in a dendrite shape is used. It contains 35 wt% of bisphenol A diglycidyl ether as a binder resin, 6 wt% of a curing agent, 0.5 wt% of a catalyst, 3 wt% of additives (coupling agent, toughening agent, curing accelerator and leveling agent), 0.5 wt% of a surfactant, and a solvent. The content of the solvent is reduced according to the content of the conductive metal particles. Graphene is not included.

[0080] Table 1

[0081]

[0082] Referring to Table 1, when conductive metal particles are used alone as metal particles, the adhesive force, sheet resistance, and processability are ensured at a content of 45 wt% to 56 wt%, but this reduces the oxidation stability, and as shown in A3 of Table 3 described later, when the high temperature stability evaluation is performed, the sheet resistance is reduced. In addition, as shown in Z5 to Z7, due to the characteristics of the dendrite shape, the conductive metal particles cannot be highly filled, and when highly filled, there are process problems such as increased viscosity and increased surface roughness of the adhesive layer.

[0083] Example 2

[0084] In the case of using silver-coated copper as the conductive metal particles, in order to observe the influence of the silver content, a binder composition including 18 wt% of the conductive metal particles, 35 wt% of bisphenol A diglycidyl ether as a binder resin, 6 wt% of a curing agent, 0.5 wt% of a catalyst, 3 wt% of an additive (coupling agent, toughening agent, curing accelerator and leveling agent), 0.5 wt% of a surfactant and 37 wt% of a solvent was prepared and used to form a bonding layer. The conductive metal particles were made to have a dendrite shape.

[0085] The adhesive layer was prepared by bar casting on a 5 μm thick copper foil to form a 20 μm wet film, drying at 80°C for 10 minutes, and curing at 180°C for 60 minutes. Table 2 shows the results of measuring the sheet resistance and adhesive force of the prepared adhesive layer, and the results of evaluating the high temperature stability by measuring the sheet resistance after heat treatment at 180°C for 300 hours under atmospheric conditions.

[0086] Table 2

[0087]

[0088] In the case of A1 in which the conductive metal particles consisted of copper alone, it was confirmed that the sheet resistance was 3.5×10 5 Ω / sq, the sheet resistance is very high, especially in the high temperature stability evaluation results, at the 300H time point, it is 8.1×10 9 Ω / sq, with a sheet resistance value that cannot be used. It was determined that this was caused by copper oxidation. In this way, when the characteristics are greatly reduced in the high-temperature stability evaluation, when the shielding film is applied to electronic components, the possibility of failure in the reflow evaluation, lead heat resistance evaluation, moisture resistance and other reliability evaluations increases significantly.

[0089] In contrast, in the case of A2 to A5 coated with silver, it was confirmed that the initial sheet resistance was about 1,000 to 1,000,000 times lower than that of pure copper, and the high temperature stability evaluation result was also 100,000 times or more lower.

[0090] On the other hand, in terms of adhesiveness, there was no difference in the content of the conductive metal particles contained in the entire adhesive composition, and no significant difference was shown among A1 and A2 to A5.

[0091] Example 3

[0092] In Example 3, the shielding layer was prepared by adjusting the content of the chemically modified graphene having an amine functional group as the first graphene in terms of the composition of A2 showing the highest performance in Preparation Example 2. The preparation was carried out in the same manner as in Example 1 except that the amount of the solvent was reduced as the first graphene was added.

[0093] The sheet resistance, adhesive force, and high temperature stability of the prepared shielding layer were evaluated, and the processability of the adhesive composition was evaluated. The results are shown in Table 3.

[0094] Table 3

[0095]

[0096] When 0.005 wt% of the first graphene is added, it is found that although the sheet resistance is slightly reduced, the high temperature stability is significantly increased. In addition, the connectivity between the conductive metal particles is improved in proportion to the content of the first graphene, so that the sheet resistance is improved. However, when more than 0.1 wt% of the first graphene is included, there is a problem that the bonding force is reduced to the expected 1.0 kgf / ㎝ or less due to excessive reaction between the first graphene and the binding resin, and in particular, the processability is significantly reduced.

[0097] Example 4

[0098] In Example 4, the shielding layer was prepared by adjusting the content of non-oxidized graphene as the second graphene in the composition of C2 showing the highest performance in Preparation Example 3. The preparation was carried out in the same manner as in Example 3 except that the amount of solvent was reduced as the second graphene was added.

[0099] The sheet resistance, adhesive force, and high temperature stability of the prepared shielding layer were evaluated, and the processability of the adhesive composition was evaluated. The results are shown in Table 4.

[0100] Table 4

[0101]

[0102] Reference Figure 4 In the case of containing less than 0.01wt% of the second graphene, the sheet resistance improvement effect is almost non-existent or very small, and in the case of containing more than 0.01wt% of the second graphene, there is an additional sheet resistance improvement effect. In particular, although not shown in the above table, there is an effect of improving moisture resistance caused by non-oxidized graphene.

[0103] However, when the content of the second graphene exceeds 1.0 wt%, not only the processability is significantly reduced, but also the bonding strength between the adhesive resins is reduced due to the side effect of the second graphene, thereby causing a problem of reduced bonding strength.

[0104] Example 5

[0105] As shown in Table 5 below, the contents of the conductive metal particles and the first graphene and the second graphene were adjusted to form an adhesive layer, and the electromagnetic shielding performance in the X-band region was confirmed using a network analyzer. The electromagnetic shielding performance represents the measured value of the shielding effectiveness in 10 GHz.

[0106] Table 5

[0107]

[0108] Referring to Table 5, it can be confirmed that D3 and D4 including the first graphene and the second graphene have higher shielding performance than D1 and D2 not including the first graphene and the second graphene.

[0109] The adhesive layer prepared by using the mixed adhesive composition for shielding electromagnetic waves of one example of the present invention described above can maintain high bonding force, and can reduce sheet resistance to improve shielding performance, thereby having the advantage of significantly improved high temperature stability. Therefore, using the adhesive composition of one example of the present invention can be expected to greatly contribute to the flexibility and thinning of the adhesive film.

[0110] The protection scope of the present invention is not limited to the description and expression of the embodiments clearly described above. Moreover, it should be noted again that the protection scope of the present invention is not limited by the known changes or substitutions in the technical field to which the present invention belongs.

Claims

1. A mixed adhesive composition for shielding electromagnetic waves, characterized in that: The invention comprises conductive metal particles, a first graphene, a binder resin and a curing agent, The first graphene is chemically modified graphene, and the binding resin is combined with the functional groups of the chemically modified graphene. The content of the conductive metal particles is 10-56wt%, the content of the first graphene is 0.005-0.1wt%, the content of the binder resin is 10-45wt%, the content of the curing agent is 1-10wt%, The mixed binder composition further comprises a second graphene, The content of the second graphene is 0.01-0.5wt%, and the second graphene is non-oxidized graphene.

2. The mixed adhesive composition for shielding electromagnetic waves according to claim 1, characterized in that: The conductive metal particles are in a flake shape or a dendrite shape.

3. The mixed adhesive composition for shielding electromagnetic waves according to claim 1, characterized in that: The functional group is at least one selected from the group consisting of an amine group, a hydroxyl group, an amide group, an azido group, an epoxy group, a thiol group, an acid anhydride group, and a carboxyl group.

4. A method for preparing a mixed adhesive for shielding electromagnetic waves, characterized in that: include: A step of preparing a first colloid in which a first graphene is dispersed; A step of pre-dispersing the first colloid and the binder resin in a solvent; A step of mainly dispersing the conductive metal particles in the pre-dispersed solvent; and The step of adding a curing agent to the solvent obtained by main dispersion to form a binder, The first graphene is chemically modified graphene, and the binding resin is combined with the functional groups of the chemically modified graphene. The content of the conductive metal particles is 10-56wt%, the content of the first graphene is 0.005-0.1wt%, the content of the binder resin is 10-45wt%, the content of the curing agent is 1-10wt%, The above step of achieving the main dispersion is performed by mixing the second colloid dispersed with the second graphene with the above solvent, The content of the second graphene is 0.01-0.5wt%, and the second graphene is non-oxidized graphene.

5. The method for preparing a mixed adhesive for shielding electromagnetic waves according to claim 4, characterized in that: The steps for preparing the first colloid include: The step of treating a graphite sheet with an oxidant and, after impregnation, irradiating microwaves to prepare expanded graphite oxide; A step of exfoliating the expanded graphite oxide to prepare graphene oxide; A step of mixing the prepared graphene oxide and deionized water to prepare a graphene oxide suspension; and A step of adding an additive for modifying graphene to the above graphene oxide suspension, stirring to cause a reaction, and then preparing a first colloid containing charged chemically modified graphene by a large-capacity circulating ultrasonic dispersion system, The above-mentioned additive is an additive capable of forming the functional group of the above-mentioned chemically modified graphene, and the functional group of the above-mentioned chemically modified graphene is at least one selected from the group consisting of amine group, hydroxyl group, amide group, azido group, epoxy group, thiol group, acid anhydride group and carboxyl group.

6. The method for preparing a mixed adhesive for shielding electromagnetic waves according to claim 4, characterized in that: The steps of preparing the second colloid include: Steps for preparing expanded graphite; A step of exfoliating the expanded graphite to prepare a graphene sheet; and The step of dispersing the exfoliated graphene flakes to prepare a second colloid.

7. A hybrid adhesive film for shielding electromagnetic waves, comprising a shielding layer and an adhesive layer, wherein the hybrid adhesive film for shielding electromagnetic waves is characterized in that: The bonding layer comprises conductive metal particles, a first graphene and a bonding resin, wherein the first graphene is a chemically modified graphene, and the bonding resin is bonded to a functional group of the chemically modified graphene. The content of the conductive metal particles is 10 to 56 wt %, the content of the first graphene is 0.005 to 0.1 wt %, and the content of the binder resin is 10 to 45 wt %. The bonding layer further comprises a second graphene. The content of the second graphene is 0.01-0.5wt%, and the second graphene is non-oxidized graphene.

Citation Information

Patent Citations

  • Conductive adhesive preparation method and conductive adhesive

    CN104099050A

  • Conductive and flame-retardative adhesive and EMI shielding film using the same

    KR1020130086902A

  • KR20200076565A